Territorial planning and Sustainable Development Goals: implementation of metrics for analyzing the Land-use planning of the municipalities of Rio do Sul, Lontras and Presidente Nereu, Santa Catarina, Brazil PLANEJAMENTO TERRITORIAL E OBJETIVOS DE DESENVOLVIMENTO SUSTENTÁVEL: IMPLEMENTAÇÃO DE MÉTRICAS PARA ANÁLISE DOS PLANOS DIRETORES DOS MUNICÍPIOS DE RIO DO SUL, LONTRAS E PRESIDENTE NEREU, SANTA CATARINA, BRASIL PLANIFICACIÓN TERRITORIAL Y DESARROLLO SOSTENIBLE: IMPLEMENTACIÓN DE MÉTRICAS PARA EL ANÁLISIS DE LOS PLANES DIRECTORES DE LOS MUNICIPIOS DE RIO DO SUL, LONTRAS Y PRESIDENTE NEREU, SANTA CATARINA, BRASIL - Kloth C.G. (2024)
© 2024 Universidade Nove de Julho-UNINOVE. All rights reserved.Objective: to measure the propensity and quality of Land-use Planning (LUP) of three municipalities in Alto Vale do Itajaí (Santa Catarina), regarding the sustainability dimensions and Sustainable Development Goals (SDGs 2015-2030). Methodology: quanti-qualitatively exploratory and documentary procedure. Three municipalities were selected for analysis, considering the regional characteristics in terms of the amount of population contingent (small, medium and large). Therefore, the propensity of the plans to meet the requirements of the dimensions of sustainability and the SDGs 2015-2030 was assessed quanti-qualitatively. Relevance: the developed methodology of quanti-qualitative analysis correlating LUPs and their propensities in meeting the dimensions of sustainability and the SDGs 2015-2030 requirements. Results: the three LUPs showed good results regarding the expectation for meeting the sustainability dimensions. However, the LUP of Rio do Sul presented a lower propensity to meet the SDGs compared to the other two municipalities analyzed. Contributions: it contributes to discussions on territorial planning and sustainable development, as well as presents a methodology for quanti-qualitative LUP analysis. Conclusion: the LUPs analysis, regards the SDGs 2015-2030, helps in the process of qualification of these, regarding sustainable development, as well as the analysis of the five dimensions of sustainability. Analyses and discussions like this are relevant as it aims to increase the relation of city development through territorial planning (LUP) and sustainability in different dimensions.